HUBUNGAN AKSEPTOR KB HORMONAL DENGAN KEJADIAN AMENORRHEA DI PUSKESMAS BOJONG KECAMATAN BOJONG KABUPATEN TEGAL TAHUN 2009 - Siswati . (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
According to Department of Planning and community family welfare Tegal regency amount akseptor KB hormonal Public Health Center  Bojong in the year 2008 is 1046 with Akseptor details akseptor needle 726 KB akseptor, implan 217 akseptor, 103 pills. From the results of the observation in the study of health Bojong KB hormonal use was much the occurrence of amenorrhea is 57 akseptor, so researchers are interested to take this case. This study aims to find out the KB akseptor incident amenorrhea with hormonal health Bojong in 2009. Design research is a study observational with cross sectional approach. Respondents who examined the  health  Bojong  in  2009  amounted  to  105  respondents.  Data  of  respondents  who experienced  amenorrhea  incidence  obtained  with  the  distribution  of  the  questionnaire  as  a data  collection  instrument  is  the  subject  of  research  akseptor  KB  hormonal  events  that experienced amenorrhea. Research in Public Health Center Bojong year 2009, was from 105 respondents  who  experienced  amenorrhea incidence  of  54.3%  and  45.7%  non  amenorrhea. Side  effects  are  influenced  by  the  hormone  progestin  in  the  hormonal  contraceptive.  This indicates a relationship with the occurrence KB hormonal amenorrhea respondents who use hormonal  KB  most  experienced  amenorrhea  incidence  of  the  57  respondents  (54,  3%). Midwives  are  expected  to  provide  IEC  about  the  factors  that  influence  the  occurrence Akseptor KB amenorrhea after hormonal and hormonal KB for the user are expected to visit after the re-use hormonal KB.